PENGARUH TATA KELOLA PERUSAHAAN, UKURAN PERUSAHAAN, TRANSAKSI HUBUNGAN ISTIMEWA TERHADAP TARIF PAJAK EFEKTIF PERUSAHAAN - Dilla Eka Aprilia; andry sugeng (Jurnal Nusa Akuntansi, 2026)
This study aims to determine the effect of Institutional Ownership and IndependentCommissioners (Corporate Governance, Company Size, and Related PartyTransactions) on a company's Effective Tax Rate. The population of this study wasenergy sector companies listed on the Indonesia Stock Exchange for the 2019-2023period. The sample size was 11 companies, obtained using purposive sampling, andobtained 55 company data observations over a five-year period. The research methodused was a quantitative method using secondary data; this type of research isassociative. The data analysis technique was multiple linear regression analysis withe-views version12. The results of this study indicate that simultaneously, InstitutionalOwnership and Independent Commissioners (Corporate Governance, Company Size,and Related Party Transactions) influence a company's Effective Tax Rate.Meanwhile, partially, Institutional Ownership and Independent Commissioners haveno effect on a company's Effective Tax Rate, and Company Size and Related PartyTransactions influence a company's Effective Tax Rate